The Fall of SVB and Its Impact on Digital Economic Transformation Efforts at Indonesia's Chair in ASEAN 2023 - ADANI, Muhammad Hilmi; KINANTI, Adelia; LABOLO, Sultan Nanta Setia Dien (PT Batara Swastika Harati, 2023)
Capitalization has forced the market to become increasingly accessible. Economic interdependence has been created and has become a principle of economics that most countries embrace. This research uses a descriptive qualitative method and a literature review to analyze opportunities and challenges that can be used as lessons for Indonesia as the holder of the ASEAN chairmanship in 2023. This method will be applied by studying related issues in various journals, books, reports and news. The collapse of the SVB significantly impacted the fall of American stocks, which subsequently affected the closure of banks inside and outside America. The implications of this phenomenon reflect ASEAN as an organization that seeks to create a stable and secure economy in the region. As the Chair of ASEAN 2023, Indonesia has many opportunities and challenges that can be taken from the fall of the banking industry in America while implementing a digital economy in the ASEAN region.